2016
DOI: 10.21595/jve.2016.16725
|View full text |Cite
|
Sign up to set email alerts
|

A review of command shaping techniques for elimination of residual vibrations in flexible-joint manipulators

Abstract: Command shaping is an important open-loop control method for improving the settling time and positioning accuracy. This technique also minimizes residual vibrations. Shaped command profiles are formed by convolving a sequence of impulses or solving special functions for the desired command signal. To determine the input shaper controller commands, estimated values of the system natural frequency and damping ratio are required to make the necessary calculations. However, real systems cannot be modelled precisel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
17
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 33 publications
(18 citation statements)
references
References 26 publications
0
17
0
Order By: Relevance
“…Regarding residual vibrations specifically, there is a sense in which all strategies for flexible system control are also about attempting to control residual vibrations. For example, see references [13][14][15][16][17][18][19][20][21][22]. In input shaping, for example, there is focus on making the controller more robust (or less sensitive) to departures of flexible system dynamics from nominal values.…”
Section: Contextmentioning
confidence: 99%
“…Regarding residual vibrations specifically, there is a sense in which all strategies for flexible system control are also about attempting to control residual vibrations. For example, see references [13][14][15][16][17][18][19][20][21][22]. In input shaping, for example, there is focus on making the controller more robust (or less sensitive) to departures of flexible system dynamics from nominal values.…”
Section: Contextmentioning
confidence: 99%
“…They reported that the vibration caused by motor motion has been reduced with the applied controller. Conker et al 21 reviewed 15 different input shapers in detail. They compared both the simulations and experimental results.…”
Section: Introductionmentioning
confidence: 99%
“…In [13], the open-loop nature of input shaping is considered for vibration control of flexible systems, in the presence of known and finite duration disturbances. Input shaping has been extensively used for vibration control (see [14] and references therein). Transient response of nonlinear systems is addressed in fewer works in the literature, with some examples being [15,16].…”
Section: Introductionmentioning
confidence: 99%